Influence of profitability on firm value: Data from transportation sector - Supitriyani Supitriyani; Astuti Astuti; Khairul Azwar (Jurnal Inovasi Ekonomi, 2022)
This study aimed to analyze and test the effect of stock returns, activity, profitability, and liquidity on firm value. We are using a sample of 14 companies obtained through the purposive sampling method on the transportation sub-sector companies listed on the Indonesia Stock Exchange. The results of this study indicate that stock returns, activity, profitability, and liquidity have a significant effect on firm value simultaneously. Partially, stock returns and profitability have a significant positive impact; activity has no significant positive impact, and liquidity has a significant negative effect on firm value.